ProspectRetrospect : Europa 1946-1976. - Buchloh, Benjamin H.D.; Fischer, Konrad; Harten, Jürgen; Matheson, John; Strelow, Hans; Kunsthalle, Düsseldorf (Köln : Verlag der Buchhandlung Walther König Köln, 1976)
Albers, Josef ; Andre, Carl ; Anselmo, Giovanni ; Arman ; Asher, Michael ; Barry, Robert ; Becher, Bernd & Hilla ; Beuys, Joseph ; Broodthaers, Marcel ; Brouwn, Stanley ; Burri, Alberto ; Calder, Alexander ; Caro, Anthony ; Charlton, Alan ; Chillida, Eduardo ; Christo ; Cotton, Paul ; Darboven, Hanne ; Dibbets, Jan ; Dubuffet, Jean ; Fautrier, Jean ; Riverhead (New York) ; Fontana, Lucio ; Francis, Sam ; Gilbert & George ; Graham, Dan ; Haacke, Hans ; Hamilton, Richard ; Hartung, Hans ; Judd, Donald ; Kawara, On ; Kelly, Ellsworth ; Klapheck, Konrad ; Klein, Yves ; Kline, Franz ; Knoebel, Imi ; de Kooning, Willem ; Kounellis, Jannis ; Kricke, Norbert ; Kuehn, Gary ; LeWitt, Sol ; Lichtenstein, Roy ; Long, Richard ; Louis, Morris ; Mangold, Robert ; de Maria, Walter ; Mathieu, Georges ; Merz, Mario ; Moore, Henry ; Morris, Robert ; Nauman, Bruce ; Noland, Kenneth ; Oldenburg, Claes ; Paolini, Giulio ; Pascali, Pino ; Penck, A.R. ; Pfahler, Karl Georg ; Polke, Sigmar ; Pollock, Jackson ; Rauschenberg, Robert ; Raysse, Martial ; Reinhardt, Ad ; Richter, Gerhard ; Riopelle, Jean -Paul ; Rosenquist, James ; Roth, Dieter ; Rothko, Mark ; Rückriem, Ulrich ; Ruthenbeck, Reiner ; Saret, Alan ; Savio, Francesco Lo ; Serra, Richard ; Smith, Tony ; Smithson, Robert ; Sonnier, Keith ; Soto, Jesus Rafael ; Stella, Frank ; Still, Clyfford ; Tàpies, Antoni ; Toroni, Niele ; Twombly, Cy ; Le Va, Barry ; Vasarely, Victor ; Villeglé, Jacques ; Warhol, Andy ; Weiner, Lawrence ; Wheeler, Doug ; Wols
Duits
ProspectRetrospect : Europa 1946-1976, Kunsthalle Düsseldorf, 20. - 31. Oktober 1976
boek
Keywords: Europa